Impact of COVID-19 Pandemic on Mental Health Among Pharmacy Students at King Abdulaziz University, Jeddah, Saudi Arabia - Badr, Aisha F.; Binmahfouz, Lenah S. (Richtmann Publishing, 2020)
Coronavirus disease (COVID-19) has spread from China to the world since December 2019. In addition to being a pandemic with mortality risk, COVID-19 affected global mental health. This study is the first to address the mental health aspects among Saudi pharmacy students during this pandemic and to explore the potential effect on their academic development. An online cross-sectional survey was distributed among 677 students from the Faculty of Pharmacy at King Abdulaziz University, Jeddah, Saudi Arabia. Participants were assessed with demographic information, the validated Generalized Anxiety Disorder 7-item (GAD-7) scale, the validated Patient Health Questionnaire-2 (PHQ-2), and multiple stress factors and motivators that might influence their academic development. Collected data were statistically analyzed. Results demonstrated that 32% of the participants were experiencing mild anxiety, 22% moderate anxiety, and 19% severe anxiety. Statistical significance in anxiety level was seen in students living alone, previously diagnosed with mental illness, and within their 4th pharmacy academic year. 49.5% of the participants were PHQ-2 positive and maybe showing symptoms of depressions. Major academic stressor for students with anxiety was their grades while major academic motivator was the coordination of each course studied. Over 70% of pharmacy students had anxiety, and half of them were PHQ-2 positive. We recommend universities to address all students’ psychological needs more often in the future, especially during a crisis like this pandemic and look into the possibility of having a Pass/Fail outcome rather than a grade-based GPA.